Dual-Processing Altruism - Kinnunen, Suna P.; Windmann, Sabine (Frontiers in Psychology, 2013)
Altruism refers to an other-benefiting behaviour that is costly but bears no direct profit to oneself. At least three different forms can be distinguished: Help giving, altruistic punishment, and moral courage. We investigated the differential impact of two thinking modes, intuitive (System 1) and rational (System 2), on these three altruistic behaviours. Situational (state-related) thinking style was manipulated via experimental instructions, and generally preferred thinking style (trait-related) was assessed via questionnaires. We found that of the subjectively preferred thinking styles (trait), faith in intuition (System 1) promoted sharing and altruistic punishment, whereas need for cognition (System 2) promoted volunteering in a situation that required moral courage. By contrast, we did not find a significant effect of situational thinking style (state) on any of the altruistic behaviours, although manipulation checks were positive. Results elucidate the affective-motivational underpinnings of different types of altruistic behaviours.